In the Translation of Language Units of Art Lexico-Semantic Properties (on the Example of French and Uzbek) - Hojiyeva Gulchehra Salimovna (Universitas Muhammadiyah Sidoarjo, 2022)
This article analyzes the role of phraseology as a field in linguistics, phraseological units formed by means of art terms in French and Uzbek languages and their lexical-semantic features on the basis of two incompatible language norms.